ORGANIZATION RESPONSABILITY TO CONSUMERS’ SATISFACTION RELATED TO THE SUPPLIED SERVICES - ISAC, Nicoleta; RĂDULESCU, Magdalena (Annales Universitatis Apulensis Series Oeconomica; Vol 1 No 16 (2014): Annales Universitatis Apulensis Series Oeconomica, 2014)
Customer satisfaction represents a modern approach for quality in enterprises and organizations and serves the development of a truly customer-focused management and culture. The purpose of this research is in finding out consumers opinions about changes within organization and how can help to adapt to changes in the economic environment in Romania. Research results follow: determining feedbak consumer regarding the services provided by organization; configuration of the managerial strategy; collecting the views of consumers on quality. Customer satisfaction measures offer a meaningful and objective feedback about client’s preferences and expectations. The research method used in this case will be an original methodological approach of customer satisfaction evaluation, using multi criteria satisfaction analysis.